Profil jaringan lunak wajah kasus borderline maloklusi klas I pada perawatan ortodonti dengan dan tanpa pencabutan gigi (Facial soft tissue profile on borderline class I malocclusion in orthodontic treatment with or without teeth extraction) - Pinandi Sri Pudyani; Yenni Hanimastuti (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2013)
Background: Determination of orthodontic treatment plan with or without teeth extraction remains controversial, especially in borderline cases, so it requires more data and information to establish appropriate treatment plans in order to obtain optimal treatment results. Purpose: The study was aimed to determine the facial soft tissue changes in the borderline class I cases treated with and without tooth extraction on post-orthodontic treatment. Methods: The study was conducted on 28 lateral cephalograms, divided into two groups; 13 cases with tooth extraction, and 15 cases without tooth extraction. The subject criterias were as follows; class I malocclusion treated with straightwire technique, skeletal class I, in range of age between 18 to 30 years old, normal overjet 2-4 mm, arch length discrepancy between 2.5 to 5 mm, Index of Fossa Canine (IFC) between 37% to 44%, did not using extraoral devices, and treated with teeth extraction of 4 second premolars or without tooth extraction. The measurement of nasolabial angle, labiomental angle, and linear position of the upper and lower lip to E-Ricketts line were done on each cephalogram before and after orthodontic treatment. Results: In teeth extraction cases, there was a change on upper and lower lips positions (p<0.05), but there were no changes on nasolabial angle and labiomental angle (p>0.05). In non teeth extraction cases, there were no changes in nasolabial angle, labiomental angle, and lips positions (p>0.05). Both of groups also have indicated that there were no changes on linear position of the upper and lower lip (p>0.05). Post-orthodontic treatment indicated a significant differences between extraction and nonextraction cases on nasolabial and labiomental angle, and lips position (p<0.05). Conclusion: The facial soft tissue profile changes on teeth extraction case was more retruded than non- teeth extraction case.Latar belakang: Penentuan rencana perawatan ortodonti dengan pencabutan atau tanpa pencabutan masih menjadi kontroversi, terutama pada kasus borderline, sehingga diperlukan lebih banyak data dan informasi untuk menetapkan rencana perawatan yang tepat agar didapatkan hasil perawatan optimal. Tujuan: Studi ini bertujuan meneliti perubahan profil jaringan lunak wajah sesudah perawatan ortodonti dengan pencabutan dan tanpa pencabutan. Metode: Pengukuran dilakukan pada 28 sefalogram lateral yang terdiri dari 2 kelompok, yaitu 13 sefalogram lateral untuk kasus dengan pencabutan gigi dan 15 sefalogram lateral untuk kasus tanpa pencabutan gigi. Kriteria subjek penelitian adalah maloklusi klas I yang dirawat dengan teknik straightwire, hubungan skeletal klas I, berusia 18–30 tahun, overjet normal antara 2–4 mm, diskrepansi panjang lengkung antara 2,5–5 mm, Indeks Fossa Canina (IFC) antara 37%-44%, tidak menggunakan alat ekstraoral, dan perawatan dengan pencabutan 4 premolar kedua atau tanpa pencabutan. Pada tiap sefalogram dilakukan pengukuran sudut nasolabial, sudut labiomental, dan pengukuran linier posisi bibir atas dan bawah terhadap garis E Ricketts sebelum dan sesudah perawatan ortodonti. Hasil: Pada kelompok pencabutan terdapat perubahan posisi bibir atas dan bawah terhadap garis E Ricketts (p<0,05), namun tidak terdapat perubahan sudut nasolabial dan sudut labiomental (p>0,05). Pada kelompok tanpa pencabutan tidak terdapat perubahan pada sudut nasolabial, sudut labiomental, dan posisi bibir (p>0,05). Terdapat perbedaan sudut nasolabial, sudut labiomental, dan posisi bibir antara kelompok dengan pencabutan dan tanpa pencabutan sesudah perawatan ortodonti (p<0,05). Simpulan: Profil jaringan lunak wajah kelompok yang dirawat dengan pencabutan gigi menjadi lebih retrusi daripada profil jaringan lunak wajah kelompok yang dirawat tanpa pencabutan.